2021
DOI: 10.1155/2021/6651238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Baduanjin Qigong Exercise on Cancer Patients: A Systematic Review and Meta-Analysis on Randomized Controlled Trials

Abstract: Objective. Baduanjin is a traditional Chinese Qigong exercise for health improvement. However, a few studies were examining the association between Baduanjin Qigong exercise and cancer patients. This study is conducted to explore the clinical effects of the Baduanjin Qigong exercise among cancer patients. Methods. We conducted a systematic review and meta-analysis using randomized controlled trials to assess the effects of the Baduanjin Qigong exercise on cancer patients. We searched Cochrane Library, PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
(14 reference statements)
1
26
0
5
Order By: Relevance
“…Publication bias was assessed using a funnel plot (Figure 3 ). It referred to the publication of studies depending on the direction and statistical significance of the results, and the first systematic investigations of publication bias focused on this aspect of the problem (Kuo et al., 2021 ). In our study, the funnel graph was asymmetric, indicating a degree of publication bias in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Publication bias was assessed using a funnel plot (Figure 3 ). It referred to the publication of studies depending on the direction and statistical significance of the results, and the first systematic investigations of publication bias focused on this aspect of the problem (Kuo et al., 2021 ). In our study, the funnel graph was asymmetric, indicating a degree of publication bias in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Qigong is a mind-body exercise originating in China which incorporates slow, coordinated movements, breath training, heightened somatic awareness, and mental focus and imagery ( Klein, 2017 ). Recent systematic reviews have suggested that Qigong may be beneficial for improving overall quality of life, mood, sleep, and symptoms such as fatigue in cancer patients ( Klein et al, 2016 ; Wayne et al, 2018 ; Kuo et al, 2021 ; Wang R. et al, 2021 ). In a pilot study conducted by our group—the parent study for the data presented here—we evaluated the impact of a 12-week Qigong intervention in BCS with PPSP.…”
Section: Introductionmentioning
confidence: 99%
“…In the West, it is sometimes used in conjunction with mainstream medicine as a supplementary tool to treat symptoms of various diseases and ailments [1][2][3][4][5][6][7][8][9][10]. Numerous studies have found that qigong can aid in the treatment of arthritis [11], back pain [12], cancer [13][14][15][16][17], cognitive impairment [18,19], Covid-19 [20,21], COPD [22], depression and anxiety [23][24][25][26], fatigue [27], hypertension [28,29], muscle strength and posture [30], Parkinson's disease [31,32], stroke [33], and tertiary-care pain management [34].…”
Section: Introductionmentioning
confidence: 99%